Motion of two point vortices in a steady, linear, and elliptical flow - Robert M. Gethner (International Journal of Mathematics and Mathematical Sciences)
For a pair of point vortices in an inviscid, incompressible fluid in the plane, the relative and absolute motion are determined when the vortices move under the influence of (1) each other, and (2) a steady, linear, and elliptical background flow.